Six sigma design, analysis and evaluation of unscheduled bogie faults in freight wagons for optimum performance and enhanced logistics management - Ayomoh, Michael (University of Pretoria, 2025)
Dissertation (MEng (Industrial Engineering))--University of Pretoria, 2024.